Kontekstualisasi Pemikiran Maqâsid Al-Sharî’ah Jasser Auda Terhadap Pendidikan Anak Usia Dini - Dahlia Dahlia (Wahana Islamika: Jurnal Studi Keislaman, 2019)
Islamic law must be oriented to the maqasid al-shari'ah, namely the benefit of mankind. However, Islamic law has always seemed rigid, so that when faced with diverse realities, it seemed unable to provide a solution. In fact, a law was made with the aim of providing comfort, security, and welfare for human life. Through a system approach, Jasser Auda offers a concept for the development of Islamic law in the current era. The system approach proposed by Jasser Auda includes six interconnected features, namely: cognitive nature; wholeness; openness; interrelated hierarchy; multi-dimensionality; and purposefulness. Jasser Auda's thoughts can be contextualized in the world of early childhood education (PAUD), for example in the internal structure of PAUD agencies, especially in the preparation of strategic plans (RENSTRA)